Radial Pattern of whole-ring Specific Gravity Variation from Pith to Bark at several Successive Height in Blue Pine (Pinus wallichiana A.B. Jackson) - Seth, M. K.; Lal, Chaman; Madhu Bala, (Indian Forester, 1988)
The paper presents the results after investigation on the radial pattern of whole-ring specific gravity variation from pith to bark to determine the magnitude at several successive heights and effects of age, distance from pith, ring width and growth rate in blue pine (Pinus wallichiana A. B. Jackson).